A Multi-Scale Review of Measurement Technologies in Electromagnetic Dosimetry: From Terminal to Environmental Exposure - Miao Cao; Tongning Wu; Zicheng Liu (Bioelectromagnetics in Medicine, 2026)
Background: With the large-scale global deployment of fifth-generation (5G) networks and the proliferation of wearable devices, electromagnetic field dosimetry faces the critical challenge of multi-scale evaluation, extending from the near-field of terminal devices to environmental exposure. Existing reviews mostly concentrate on a single spatial domain, leaving a cross-scale synthesis conspicuously absent. This paper systematically reviews recent technical advancements in dosimetry measurement technologies across both terminal and environmental levels to provide a comprehensive reference for standardization and engineering practice. Methods: The technical literature and regulatory standards in this review are structured along two distinct spatial dimensions to benchmark electromagnetic dosimetry measurement technologies. At the terminal level, this work examines the technological evolution of specific absorption rate evaluation below 6 GHz and incident/absorbed power density measurements above 6 GHz, focusing on probe-based measurement technologies, analytical and data-driven field reconstruction algorithms, and infrared thermography. At the environmental level, broadband and frequency-selective measurement techniques are evaluated based on their operational principles. Advanced surrogate modeling frameworks, prominently represented by polynomial chaos expansion and Kriging, are analyzed regarding their application to uncertainty propagation in high-dimensional dynamic environments. Results: At the terminal level, SAR evaluation has evolved toward rapid multi-probe arrays and non-invasive over-the-air systems, achieving higher evaluation efficiency. For millimeter-wave bands, field reconstruction algorithms have emerged as a dominant route to evaluate power density, while infrared thermography achieves a speed increase. At the environmental level, the technical watershed between broadband screening and frequency-selective techniques lies in their divergent orientations toward computational efficiency versus source parsing accuracy. Notably, 5G code-selective measurement represents a major paradigm shift from conventional frequency-domain scanning to signal-level decoding. For uncertainty quantification, surrogate models successfully extend parameter analysis to highly dynamic beamforming scenarios. However, an integrated validation framework linking terminal and environmental domains remains absent, and a globally unified standardization procedure for dynamic network assessments has yet to be established. Conclusions: The evolution of electromagnetic dosimetry measurement technologies demonstrates clear trajectories toward higher speed, superior precision, enhanced intelligence, and dynamic adaptability. To bridge the gap between terminal compliance and real-world population exposure, future research should prioritize the deep integration of artificial intelligence with physics-informed measurement methods, non-invasive real-time continuous monitoring, and emerging dosimetry techniques within the 6G terahertz band.